2022
DOI: 10.1038/s41598-022-25998-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cuproptosis-related long noncoding RNA signature for predicting prognosis and immunotherapy response in bladder cancer

Abstract: Bladder cancer (BC) is the most common malignant tumour of the urinary system and one of the leading causes of cancer-related death. Cuproptosis is a novel form of programmed cell death, and its mechanism in tumours remains unclear. This study aimed to establish the prognostic signatures of cuproptosis-related lncRNAs and determine their clinical prognostic value. RNA sequencing data from The Cancer Genome Atlas were used to detect the expression levels of cuproptosis-related genes in BC. Cuproptosis-related l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
1
0
1
Order By: Relevance
“…Based on TCGA RNA sequencing data, the CIBERSORT tool was used to analyze 22 immune cell components, including B cells, T cells, natural killer cells, macrophages, and dendritic cells in medium tumor samples. 16 The p<0.05 indicated that the cell components inferred from the samples had high credibility. Pearson analysis was performed to correlate different immune cells and risk scores.…”
Section: Methodsmentioning
confidence: 99%
“…Based on TCGA RNA sequencing data, the CIBERSORT tool was used to analyze 22 immune cell components, including B cells, T cells, natural killer cells, macrophages, and dendritic cells in medium tumor samples. 16 The p<0.05 indicated that the cell components inferred from the samples had high credibility. Pearson analysis was performed to correlate different immune cells and risk scores.…”
Section: Methodsmentioning
confidence: 99%
“…膀胱癌是起源于尿路上皮的恶性肿瘤,是我国泌尿系统肿瘤所致死亡的最常见原因 [ 1 ] 。膀胱癌的治疗方案包括手术切除、放化疗和免疫治疗等,尽管这些治疗方法近年来取得了显著进展,但患者治疗后复发或进展的可能性仍较高,其中约40%的患者会多次复发 [ 2 ] 。目前临床上膀胱癌患者的预后主要通过组织病理学诊断和肿瘤分期系统进行预测,但准确度不高。虽已有多个研究通过TCGA和GEO等公共数据库构建膀胱癌预后模型,但仍无法同时满足方便快捷和高准确率的要求 [ 3 - 5 ] 。因此,建立膀胱癌患者预后的高效预测模型,对于指导临床个性化治疗十分必要。…”
unclassified